Application of a SCOBA in Educational Praxis of L2 Written Argumentative Discourse. (10th June 2021) - Hadidi, Ali
Abstract : The purpose of this study was to examine if and the way in which a central argumentative discourse schema, as a cognitive tool, was appropriated by an English language learner. There has been little research on the development of L2 written argumentative discourse after a period of instruction and no study, to my knowledge, examining and detailing a systematic pedagogy for L2 learners. Grounded in both C-BLI (concept-based language instruction) and cognitive-process theory of writing (Bereiter and Scardamlaia, 1987), the present study details the appropriation of a central Toulmin (1958/2003) SCOBA, 'schema for complete orientating basis of an action, ' (Gal'perin, 1989: 70) to mediate the cognitive processes leading to the production of texts that feature argumentative discourse features. The central Toulmin SCOBA and the text generation artifacts that were (co-) constructed during C-BLI will be examined and evidence will be provided for the effectiveness of the SCOBA. There will be a theoretical and empirical discussion of how the SCOBA and its related artifacts made the-rule-of thumb (Negueruela, 2003) and amorphous idea (Vygotsky, 1986) of thesis-support scientific and discrete. In order to guide the teaching-learning of written argumentative discourse, the cognitive processes of writing were conceptualized as mental actions (Gal'perin, 1989). The findings indicate that the learner's cognitive processes of composing and the quality of his texts improved during and after instruction.